Distortion of DNA Origami on Graphene Imaged with Advanced TEM Techniques. Issue 31 (16th June 2017) - Kabiri, Yoones; Ananth, Adithya N.; van der Torre, Jaco; Katan, Allard; Hong, Jin‐Yong; Malladi, Sairam; Kong, Jing; Zandbergen, Henny; Dekker, Cees
Abstract : While graphene may appear to be the ultimate support membrane for transmission electron microscopy (TEM) imaging of DNA nanostructures, very little is known if it poses an advantage over conventional carbon supports in terms of resolution and contrast. Microscopic investigations are carried out on DNA origami nanoplates that are supported onto freestanding graphene, using advanced TEM techniques, including a new dark‐field technique that is recently developed in our lab. TEM images of stained and unstained DNA origami are presented with high contrast on both graphene and amorphous carbon membranes. On graphene, the images of the origami plates show severe unwanted distortions, where the rectangular shape of the nanoplates is significantly distorted. From a number of comparative control experiments, it is demonstrated that neither staining agents, nor screening ions, nor the level of electron‐beam irradiation cause this distortion. Instead, it is suggested that origami nanoplates are distorted due to hydrophobic interaction of the DNA bases with graphene upon adsorption of the DNA origami nanoplates. Abstract : Using advanced transmission electron microscopy techniques, DNA origami nanostructures that are deposited onto different substrates such as atomically thin graphene, functionalized graphene, and carbon are visualized. It is observed that the DNA nanostructures are distorted when deposited onto graphene, while no such distortion is seen on carbon, which is likely due to π–π interaction of DNA bases with graphene.